Familial clustering of primary lateral sclerosis and amyotrophic lateral sclerosis: Supplementary evidence for a continuum. (23rd June 2021) - Corcia, Philippe; Lunetta, Christian; Couratier, Philippe; Vourc'h, Patrick; Gromicho, Marta; Desnuelle, Claude; Soriani, Marie‐Hélène; Pinto, Susana; de Carvalho, Mamede
Abstract: Background and purpose: Primary lateral sclerosis (PLS) is a motor neuron disorder characterized by a pure upper motor neuron degeneration in the bulbar and spinal regions. The key difference with amyotrophic lateral sclerosis (ALS) is the lower motor neuron system integrity. Despite important literature on this disease, the pathophysiology of PLS remains unknown, and the link with ALS still balances between a continuum and a separate entity from ALS. Methods: We report nine families in which both PLS and ALS cases occurred, in general among first‐degree relatives. Results: The patients with PLS and ALS had a typical disease presentation. Genetic studies revealed mutations in SQSMT1, TBK1, and TREM2 genes in two PLS patients and one ALS patient. Conclusions: These results strongly support a phenotypic continuum between PLS and ALS.